Efficacy of obstructive sleep apnea treatment by antileukotriene receptor and surgery therapy in children with adenotonsillar hypertrophy: A descriptive and cohort study - Tran-Minh, Dien; Phi-Thi-Quynh, Anh; Nguyen-Dinh, Phuc; Duong-Quy, Sy (Frontiers in Neurology, 2022)
Background: Prevalent of obstructive sleep apnea (OSA) in children with adenotonsillar hypertrophy is high and related to the occlusion of the upper airway. The main treatments of OSA in these children is adenotonsillectomy. However, the indications of tonsillectomy remain debatable and non- invasive treatment is still a potential choice in these patients. Methods: It was a cross-sectional and interventional study. This study included children aged from 2 to 12 years-old who were diagnosed with OSA by respiratory polygraphy and had tonsillar hypertrophy with/without adenoid hypertrophy. Physical examination and endoscopy were done to evaluate the size of tonsillar and adenoid hypertrophy by using Brodsky and Likert classifications, respectively. The severity of OSA was done by using the classification of AHI severity for children. Results: There were 114 patients (5.5 ± 2.1 years) included in the present study. The main reasons for consultations were snoring (96.7%), a pause of breathing (57.1%), an effort to breathe (36.8%), unrefreshing sleep (32%), doziness (28.2%), and hyperactivity (26.3%). There were 36% of subjects with tonsillar hypertrophy grade 2, 48.2% with grade 3; among them, there were 46.5% of subjects with grades 1-2 of adenoid hypertrophy and 45.6% with grade 3. The mean AHI was 12.6 ± 11.2 event/h. There was a significant correlation between the mean AHI and the level of tonsillar and adenoid hypertrophy severity (r = 0.7601 and r = 0.7903; p < 0.05 and p < 0.05, respectively). The improvement of clinical symptoms of study subjects was found in both groups treated with ALR (antileukotriene receptor) or ST (surgery therapy). The symptoms related to OSA at night were significantly improved after treatment with ATR and with ST (p<0.001 and p=0.001, respectively; Table 3). The mean AHI was significantly reduced in comparison with before treatment in study subjects treated with ALR (0.9 ± 1.0 vs 3.9 ± 2.7 events/hour; p=0.001) or with ST (3.5 ± 1.4 vs 23.4 ± 13.1 events/hour; p<0.001). Conclusion: The treatment of OSA due to adeno-tonsillar hypertrophy with ALR for moderate OSA or surgery for severe OSA might reduce the symptoms related to OSA at night and during the day.